OPTIMIZATION OF VARIABEL HELIX ANGLE PARAMETERS IN CNC MILLING OF CHATTER AND SURFACE ROUGHNES USING TAGUCHI METHOD - Hardinsi, Festo Andre; Novareza, Oyong; Sonief, Achmad As’ad (JEMIS (Journal of Engineering & Management in Industrial System), 2021)
In the manufacturing industries, the main problem in process of operating CNC milling machine was chatter effect (self-excited vibration) which increases the quality of the surface roughness. In this study is to determine optimal value of parameters for chatter and surface roughness. The chatter measured using accelerometer MPU-6050 with Arduino by software LabVIEW-2019 based on peaks-FFT value and the surface roughness measured by SJ-301 tester. The research parameters like variable helix angle, spindle speed, feed rate, and depth of cut using stainless steel 304 by Taguchi method. The optimum parameters value obtained are variable helix 35/38 degrees, spindle speed 3000 RPM, feed rate 150 mm/min and depth of cut 0.4 mm. Based on ANOVA value, the variable helix angle and depth of cut are found to be significant for chatter and surface roughness. The depth of cut was high contribution by ANOVA chatter by 93.84% and surface roughness by 91.93%.